2019
DOI: 10.1002/mbo3.836
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic comparison of aerial and submerged mycelia formed in the liquid surface culture of Cordyceps militaris

Abstract: An entomopathogenic fungus, Cordyceps sp. has been known to produce cordycepin which is a purine nucleoside antimetabolite and antibiotic with potential anticancer, antioxidant and anti‐inflammatory activities. Interestingly, Cordyceps militaris produces significantly higher amount in a liquid surface culture than in a submerged culture. The liquid surface culture consists of mycelia growing into the air (aerial mycelia) and mycelia growing toward the bottom into the medium (submerged mycelia). In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Based on the large number of upregulated genes shared between "Spruce + board anaerobic" and "Malt extract" cultivations, we concluded that the submerged mycelium might encounter hypoxia under non-agitated conditions. Similar outcome was recently reported for the Ascomycota species Cordyceps militaris [48]. This is consistent with minor ethanol accumulation detected from liquid media under aerobic cultivations.…”
Section: Adaptation To Hypoxia By Regulation Of Intracellular Metabolismsupporting
confidence: 91%
“…Based on the large number of upregulated genes shared between "Spruce + board anaerobic" and "Malt extract" cultivations, we concluded that the submerged mycelium might encounter hypoxia under non-agitated conditions. Similar outcome was recently reported for the Ascomycota species Cordyceps militaris [48]. This is consistent with minor ethanol accumulation detected from liquid media under aerobic cultivations.…”
Section: Adaptation To Hypoxia By Regulation Of Intracellular Metabolismsupporting
confidence: 91%
“…This explains why C. militaris cultivated in pupae had a high content of cordycepin. In addition, it is consistent with the fact that static submerged liquid fermentation can obtain a higher yield of cordycepin than liquid fermentation with ventilation does (Suparmin et al, 2017(Suparmin et al, , 2019. Static liquid fermentation also induced hypoxia stress in the cells of these submerged mycelia.…”
Section: Discussionsupporting
confidence: 83%
“…However, the functions of hypoxia and its regulators have not been well investigated in C. militaris. In a previous study, only increased expression levels of the genes involved in the ergosterol biosynthetic pathway were reported in hypoxic submerged mycelia, but not of genes encoding SREBPs (Suparmin et al, 2019). Therefore, the investigation of exogenous vgb and endogenous SREBPs-related genes is helpful to better understand the regulatory role of hypoxia stress in the growth and biosynthesis of bioactive compound in C. militaris.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, cordycepin and other secondary metabolites may be important for fungal growth in larvae. Our previous paper shows that the expression of CCM_01285 decreased in aerial and submerged mycelia during cordycepin production in the static cultivation of C. militaris [ 14 ]. The expression of CCM_01285 may be unrelated to cordycepin production.…”
Section: Resultsmentioning
confidence: 99%
“…More cordycepin is produced in static than in submerged culture. Transcriptomic analysis indicates that hypoxic conditions in static cultivation may be required for the production of cordycepin [ 13 , 14 ]. This result suggests that cordycepin is produced in vivo in the hemocoel of silkworms during the infection.…”
Section: Introductionmentioning
confidence: 99%